Inpatient vs Outpatient Evaluation of Suspected Paraneoplastic Cerebellar Degeneration. Issue 1 (February 2021) - Witek, Natalie; Afshari, Mitra; Liu, Yuanqing; Ouyang, Bichun; Hall, Deborah
Abstract : Objective: To determine the differences in outcomes of adult patients with ataxia initially evaluated for paraneoplastic cerebellar degeneration (PCD) as inpatients or outpatients. Methods: In this retrospective cohort analysis, diagnosis, workup, and functional outcomes based on the change in the modified Rankin Scale (mRS) score were compared between patients with ataxia who underwent workup for PCD initially as inpatients vs outpatients between March 2011 and June 2018 at Rush University Medical Center. Results: There were 78 patients included in the analysis; 59% were women, and the average age at symptom onset was 57 ± 19.5 years. Nineteen patients (24.3%) underwent evaluation as inpatients and 59 (75.6%) as outpatients. Admitted patients were more likely to receive immunotherapy (73.7% vs 20.3%, p < 0.0001) and received it faster than outpatients (0.40 months for inpatients, interquartile range [IQR] 0.03–1 months, vs 6.6 months for outpatients, IQR 2–11.7 months; p = 0.01). A greater percentage of inpatients improved based on the mRS score compared with those who underwent evaluation as outpatients (52.63% vs 22.81%, p = 0.01). Conclusions: More patients improved from baseline in the inpatient cohort. Classification of Evidence: This study provides Class III evidence that for patients undergoing initial evaluation for PCD, patients undergoing inpatient evaluation have better outcomes compared with those undergoing outpatient evaluation.